2013
DOI: 10.1021/nn402416h
|View full text |Cite
|
Sign up to set email alerts
|

Negatively Charged Metal Oxide Nanoparticles Interact with the 20S Proteasome and Differentially Modulate Its Biologic Functional Effects

Abstract: The multicatalytic ubiquitin-proteasome system (UPS) carries out proteolysis in a highly orchestrated way and regulates a large number of cellular processes. Deregulation of the UPS in many disorders has been documented. In some cases, e.g. carcinogenesis, elevated proteasome activity has been implicated in disease development, while the etiology of other diseases, e.g. neurodegeneration, includes decreased UPS activity. Therefore, agents that alter proteasome activity could suppress as well as enhance a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Clearly, the degree of conformational change upon binding depends on both the structure and chemistry of the protein, as well as on the physico-chemical characteristics of the NP. 215,217 Collectively, these data indicate that, in contrast to bulk materials, a certain binding specificity of nano-sized objects for a specific (class of) protein(s), and also other biomolecules may exist. proteins with strong internal stabilizing forces such as salt bridges or disulfide bonds, are expected to be less affected upon binding.…”
Section: Review Articlementioning
confidence: 94%
“…Clearly, the degree of conformational change upon binding depends on both the structure and chemistry of the protein, as well as on the physico-chemical characteristics of the NP. 215,217 Collectively, these data indicate that, in contrast to bulk materials, a certain binding specificity of nano-sized objects for a specific (class of) protein(s), and also other biomolecules may exist. proteins with strong internal stabilizing forces such as salt bridges or disulfide bonds, are expected to be less affected upon binding.…”
Section: Review Articlementioning
confidence: 94%
“…Indeed, the ability of C 60 fullerenes to sustain the autonomous kinase activity of CaMKII may have significant implications for both the safety and for potential therapeutic applications of fullerenes, and further studies are warranted. Moreover, a recent in vitro study revealed that several types of metal oxide nanoparticles adsorbed to the various subunits of the proteasome and that the nanoparticles modulated the function of the proteasome in a manner dependent on their size and surface charge (and dose) (27). The ubiquitin-proteasome system is responsible for the controlled degradation of the majority of proteins in the cell, thereby regulating most cellular processes.…”
Section: Towards a Molecular Nanotoxicologymentioning
confidence: 99%
“…Earlier reports indicate that the NP surface charge is a contributing factor for protein adsorption onto NPs via electrostatic interaction. [19][20][21][22][23][24][25] In ZnO NPs, V O is the most cited surface defects, and its presence results in a positively charged surface. 26 A recent study on cerium oxide NPs by Lee et al revealed that V O clustered at the surface of NPs have a size dependent antioxidant activity and smaller diameter NPs (containing more surface V O ) were found to posses high antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%